Idiopathic granulomatous mastitis associated with risperidone-induced hyperprolactinemia - Lin, Chih-Hsun (BioMed Central, 2012)
Idiopathic granulomatous mastitis (IGM) is a rare inflammatory breast disease. The etiology and treatment options of IGM remain controversial. Previous case reports have suggested that hyperprolactinemia may be associated with IGM. In the present report, we describe the first case of IGM associated with risperidone-induced hyperprolactinemia. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/8120093785928228